Neonatal acute kidney injury in a tertiary care hospital in Kashmir, Jammu and Kashmir, India - Ashraf, Mohd; Bhat, Firdous Ahmed; Tak, Shafat Ahmed; Iqbal, Javaid; Kambay, Altaf Hussain; Riyaz, Anisa (Indian Journal of Child Health, 2019)
Background: Acute kidney injury (AKI) is a common entity in neonates admitted to the neonatal intensive care unit (NICU). Neonatal AKI is associated with increased morbidity and mortality and a greater risk of chronic kidney disease among the affected ones in future. Objectives: The objectives of this study were to study the incidence and outcome of neonatal AKI in our NICU. Materials and Methods: This single-center retrospective study included all infants who were admitted in a tertiary care hospital, J and K, from June 2013 to May 2014. Neonates, who had known congenital kidney diseases or if they did not survive beyond the first 48 h of life or had a hospital stay for